Pemberian Ekstrak Kulit Mangga Arumanis (Magnifera Indica L.) Berpengaruh Terhadap Kadar Asam Urat Pada Tikus Putih Jantan (Rattus Norvegicus) - Arfah, Arni Isnaini; Rachman, Mochammad Erwin; Nazaruddin, Andi Muhammad Ariansyah; Fattah, Nurfachanti (Rumah Sakit Ibnu Sina, Makassar, 2021)
Uric acid is the result of metabolism produced by the body, but the rest of the metabolism of protein foods containing purines can also produce uric acid. Hyperuricemia is a condition where there is an increase in uric acid levels. The normal concentration of uric acid is 7.0 mg/dL for men and 6.0 mg/dL for women. Hyperuricemia occurs due to the high consumption of foods containing purines, lowering it can be done by reducing the production or increasing the excretion of uric acid. Mango skin contains flavonoid components and mangiferin antioxidants which are good for the body as a protector against certain diseases. The purpose of this study was to determine the effect of giving mango arumanis peel extract (Magnifera indica L.) on uric acid levels in male white rats (Rattus norvegicus). This type of research is true experimental pre-post test group design, using a group of 20 experimental animals with 10 animals each/group induced by chicken liver juice and potassium oxonate and 10 control groups given a placebo. The control group was given a placebo Na CMC 2 g/dl and the treatment group was given mango arumanis peel extract 83 mg/dl with a total intervention of 14 days. The results showed uric acid levels in the blood of rats (on the 8th day of administration of mango arumanis peel extract was 9.46 mg/dl and on the 15th day it was 1.89 mg/dl. There was a significant difference in uric acid levels, namely the group The control group is 3.5 mg/dl and the treatment group is 1.8 mg/dl. So, there is an effect of Arumanis mango peel extract in lowering blood uric acid levels in male rats.